Prevalence and Impact of Constipation on Reconstructive Outcomes Following Endoscopic Skull Base Surgery - Nguyen, Theodore V.; Hong, Ellen M.; Bitner, Benjamin F.; Chernyak, Michelle; Chan, Daniella; Dilley, Katelyn K.; Abiri, Arash; Li, Ji Y.; Torabi, Sina J.; Pang, Jonathan C.; Hsu, Frank P.K.; Kuan, Edward C. (Journal of Neurological Surgery Part B: Skull Base, 2024)
Postoperative constipation in endoscopic skull base surgery (ESBS) may provoke undesired straining, which, in theory, may create intracranial pressure shifts and impact skull base reconstruction. The purpose of this study is to assess the prevalence and contributing factors to postoperative constipation after ESBS, and whether this impacts reconstructive outcomes.Patients undergoing ESBS between July 2018 and December 2022 at a single-center, tertiary academic skull base surgery program were retrospectively reviewed. Chart reviews were performed to identify average bowel movements per day, indication for surgery, age, sex, body mass index (BMI), history of chronic pain, length of postoperative bedrest, length of stay (LOS), and postoperative use of opioid analgesics. Additionally, use of a standing stool bowel regimen, as-needed (PRN) stool softeners/laxatives, and enemas were recorded. Constipation was defined as greater than 48 hours without a bowel movement.In total, 213 patients (115 with intradural pathologies) were identified, of which 146 (69%) patients had postoperative constipation. Postoperative constipation was associated with longer bedrest (1.86 ± 0.20 vs. 1.06 ± 0.12 days; p = 0.011); increased morphine equivalent dose (MED) during postoperative days 2, 3, 5, and 6 (all p < 0.05); and total postoperative MED (106.70 ± 14.01 vs. 46.88 ± 8.44 mg; p < 0.001). Additionally, postoperative constipation was an independent predictor of LOS (p = 0.009). There were no differences in postoperative cerebrospinal fluid (CSF) leak between the groups (p = 0.622).Postoperative constipation rates were high after ESBS and likely causative factors include increased immobilization and postoperative opioid use. Standing bowel regimens should be considered in ESBS patients. However, there was no increased rate of postoperative CSF leaks.
Keywords: skull base reconstruction outcomes; postoperative; analgesia; opioid; constipation; CSF leak